LINGUAPRAGMATIC TRANSFORMATION OF ENGLISH AND UZBEK PHRASEOLOGICAL UNITS (Ustozlar uchun, 2026)
This article explores the linguapragmatic changes of English and Uzbek phraseological units in the process of translation and intercultural communication. The phraseological expressions reflect the national culture, traditions. Therefore, translating them requires both linguistic accuracy and pragmatic adaptation. The research investigates semantic, stylistic, and pragmatic transformations that occur while translating idioms, proverbs, and fixed expressions between English and Uzbek.  Particular emphasis is placed on equivalence, contextual interpretation, communicative purpose, and cultural characteristics. It concludes that effective translation of phraseological units depends on maintaining not only their semantic meaning but also their pragmatic and communicative impact in the target language.